2020
DOI: 10.1177/0271121420935579
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Classroom-Wide Social–Emotional Interventions for Preschool Children

Abstract: Background: All children benefit from intentional interactions and instruction to become socially and emotionally competent. Over the past 30 years, evidence-based intervention tactics and strategies have been integrated to establish comprehensive, multitiered, or hierarchical systems of support frameworks to guide social–emotional interventions for young children. Objectives: To review systematically the efficacy of classroom-wide social–emotional interventions for improving the social, emotional, and behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 78 publications
1
47
0
1
Order By: Relevance
“…However, some differences emerged. Luo et al (2020) identified and screened more than twice the number of records (n 30 361) compared to Blewitt et al (2018) (n 13 035). The number of full-text articles assessed for eligibility were similar (Blewitt et al, 2018, n 362 vs. Luo et al, 2020 but in the final stage, Blewitt et al (2018) included approximately twice the number of studies (n 79) compared to Luo et al (2020) (n 39).…”
Section: Search Strategy Selection Data Extraction and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…However, some differences emerged. Luo et al (2020) identified and screened more than twice the number of records (n 30 361) compared to Blewitt et al (2018) (n 13 035). The number of full-text articles assessed for eligibility were similar (Blewitt et al, 2018, n 362 vs. Luo et al, 2020 but in the final stage, Blewitt et al (2018) included approximately twice the number of studies (n 79) compared to Luo et al (2020) (n 39).…”
Section: Search Strategy Selection Data Extraction and Analysismentioning
confidence: 99%
“…Luo et al (2020) identified and screened more than twice the number of records (n 30 361) compared to Blewitt et al (2018) (n 13 035). The number of full-text articles assessed for eligibility were similar (Blewitt et al, 2018, n 362 vs. Luo et al, 2020 but in the final stage, Blewitt et al (2018) included approximately twice the number of studies (n 79) compared to Luo et al (2020) (n 39). The differences could be attributed to diverging choices of databases where Blewitt et al (2018) included a database covering biomedical and health research (MEDLINE Complete), while Luo et al (2020) chose to search the multidisciplinary Academic Search premier, which does not have a medical focus, and the Education Full Text database, which covers education and related fields of research.…”
Section: Search Strategy Selection Data Extraction and Analysismentioning
confidence: 99%
See 3 more Smart Citations